REVIEW JURNAL PENGELOLAAN LIMBAH PADAT, CAIR, DAN GAS DALAM INDUSTRI FARMASI REVIEW OF JOURNAL OF SOLID, LIQUID, AND GAS WASTE MANAGEMENT IN PHARMACEUTICAL INDUSTRY - Yuspa, Nor Latifah; Yulianita Pratiwi Indah Lestari (Jurnal Cakrawala Ilmiah, 2024)
Pharmaceutical industry waste management is a critical aspect in maintaining environmental and public health. Waste from the pharmaceutical industry includes potentially hazardous solid, liquid, and gaseous wastes. Various management methods have been developed, such as inertization, safe stockpiling, incineration, encapsulation, and deep burial for solid waste; chemical disinfection, sewer disposal, and treatment in wastewater treatment plants for liquid waste; and waste gas treatment technologies for gaseous waste. In Indonesia, PT Indofarma Tbk in Bekasi has implemented various stages of waste management, including reduction, reuse, containerization and collection, internal transportation, internal treatment, temporary storage, external transportation, and outplant treatment. This study used a qualitative methodology with a literature review from the Scopus and SINTA databases, and the results were presented in a descriptive narrative. In conclusion, effective pharmaceutical waste management is essential to minimize negative impacts on the environment and public health.